2011
DOI: 10.1007/s10388-011-0302-8
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise overexpression of p63, p53, and cytokeratin 14 during progression of esophageal squamous intraepithelial neoplasia: useful immunohistochemical markers for differential diagnosis

Abstract: Background Esophageal squamous intraepithelial neoplasia (ESIN) as a precursor for invasive carcinoma is classified into low-grade IN (LIN) and high-grade IN (HIN), the latter including carcinoma in situ (CIS). Increasing grades of ESIN are associated with increasing risk of invasive carcinoma, but differentiation among LIN, HIN, and CIS is subjective and challenging. As p63, a member of the p53 family, is known to regulate differentiation and proliferation in epithelial progenitor cells, its expression, along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Contrast to these findings, Nakayama et al (2011) reported increased expression of CK14 as squamous intraepithelial neoplasia progressed with the greatest expression observed in CIS [54]. Similar results were identified in other studies about invasive salivary adenoid cystic carcinoma and breast cancer [55], [56].…”
Section: Ck 14 Role In Determining Bladder Cancer Gradingsupporting
confidence: 85%
“…Contrast to these findings, Nakayama et al (2011) reported increased expression of CK14 as squamous intraepithelial neoplasia progressed with the greatest expression observed in CIS [54]. Similar results were identified in other studies about invasive salivary adenoid cystic carcinoma and breast cancer [55], [56].…”
Section: Ck 14 Role In Determining Bladder Cancer Gradingsupporting
confidence: 85%